Impact of the COVID-19 Pandemic on the Psychological Well-Being of Health Care Professionals in India - Hiba Siddiqui; Shubham Garg; Pramod Kumar Julka; Aditi Chaturvedi; Sharan Choudhri; Ramandeep Singh Arora (Indian Journal of Medical and Paediatric Oncology)
Introduction and Objective Health care professionals (HPs) have been at the forefront facing the pressures and uncertainties of the COVID-19 pandemic, and thus have a higher psychological vulnerability. The incidence of psychological distress, which can negatively affect an HP's work efficiency and long-term well-being, has not been studied in depth in India.